Pro-active game-based neurofeedback training of parietal alpha rhythm - Aksiotis, Vladislav; Ossadtchi, Alexei (2021 Third International Conference Neurotechnologies and Neurointerfaces (CNN), 2021)
The use of Neurofeedback (NFB) as a therapeutic tool remains controversial. Its efficacy is subject to many factors including subject's motivation, content of the instruction, resting-state amplitude before the training and subject's ability to concentrate on the task. Here we introduce a novel proactive neurofeedback paradigm and explore its use for training t 0 increase parietal alpha rhythm power in a visually rich gamified environment. Hybrid control (a keyboard with alpha rhythm), mixed feedback delivery (discrete and continuous), gamified procedure and decreased feedback delay are supposed to engage the subject and positively influence the training outcome. Results show a gradually ascending learning curve and significant differences between baselines in the real feedback group compared to a control group with fake feedback after only 30 minutes of the entertainful training. Overall, as demonstrated by our pilot study with 20 participants, the novel proactive paradigm appeared to be an efficient and engaging tool for conditioning parietal alpha power. The subjects from the experimental group show significant growth in the incidence rate of alpha bursts over the course of training as well as exhibit sustainable changes in the post-training interval. Such a gamified way for conditioning brain activity could pave a road for the future non-pharmacological treatment of a broad range of neurodegenerative disorders and achievement of peak cognitive performance.